2005
DOI: 10.1139/a05-009
|View full text |Cite
|
Sign up to set email alerts
|

Liming for the mitigation of acid rain effects in freshwaters: A review of recent results

Abstract: Acid rain has affected freshwater ecosystems for more than 50 years in much of northern Europe and North America. The acidification of waters, along with concurrent reduction in acid neutralization capacity, has caused deleterious changes to aquatic populations in much of these regions. To reverse some of the changes to aquatic ecosystems, a number of governmental and nongovernmental groups have applied lime and other neutralizing substances to streams, rivers, lakes, and catchments in the most affected or mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 179 publications
(222 reference statements)
4
82
0
1
Order By: Relevance
“…River A T originates from erosion and is correlated with bedrock composition (e.g., McGrath et al, 2016). Positive trends in river A T have been documented in North America and occur via a number of processes including (1) the interplay of rainfall and land use (Raymond and Cole, 2003), (2) anthropogenic limestone addition used to enhance agricultural soil pH (Oh and Raymond, 2006;Stets et al, 2014) and freshwater pH (Clair and Hindar, 2005), and (3) potentially indirect effects of anthropogenic CO 2 on groundwater CO 2 acidification and weathering (Macpherson et al, 2008). These and other processes were hypothesized to have driven A T changes in the Baltic Sea (Müller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…River A T originates from erosion and is correlated with bedrock composition (e.g., McGrath et al, 2016). Positive trends in river A T have been documented in North America and occur via a number of processes including (1) the interplay of rainfall and land use (Raymond and Cole, 2003), (2) anthropogenic limestone addition used to enhance agricultural soil pH (Oh and Raymond, 2006;Stets et al, 2014) and freshwater pH (Clair and Hindar, 2005), and (3) potentially indirect effects of anthropogenic CO 2 on groundwater CO 2 acidification and weathering (Macpherson et al, 2008). These and other processes were hypothesized to have driven A T changes in the Baltic Sea (Müller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The specific goals of liming streams or catchments are to increase stream ANC, pH and Ca while decreasing SO 4 and Al. Restoration practices include adding lime directly to stream water or treating the entire catchment with reported lime additions ranging from 5 to 30 Mg ha À1 (Clair and Hindar, 2005). Our estimated lime additions fall within this broad range, with 11.6-21.1 Mg ha À1 CaCO 3 required to increase the top 30 cm of soil to pH 5.5.…”
Section: Catchment Liming and Mitigationmentioning
confidence: 77%
“…In an extensive literature review, Clair and Hindar (2005) examined liming experiments conducted from the 1980s to 2000, including various chemical compounds and methods of application. Overall, their review found that directly adding lime to the stream channel significantly improved the stream pH, chemistry, and suitability for fish populations.…”
Section: Catchment Liming and Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liming has been used for decades to counter impacts of acid rain in northern hemisphere countries like Sweden (Bengtsson et al 1980), although Clair and Hindar (2005) detail limitations to this remediation method. Stockner and MacIsaac (1996) observe benefits of a nutrient enrichment programme in British Columbia.…”
Section: Options For Environmental Water Demand Managementmentioning
confidence: 99%